2012
DOI: 10.1007/s11250-012-0313-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the genetic diversity among native Turkish sheep breeds using mtDNA polymorphisms

Abstract: A total of 135 unrelated sheep from nine Turkish native sheep breeds (Daglıc, Kivircik, Imroz, Chios, Morkaraman, Ivesi, Hemsin, Karayaka and Akkaraman) were investigated to determinate the maternal genetic diversity using a sequence of a 531-bp segment of the mtDNA control region. Analysis of the mtDNA control region sequence revealed 63 haplotypes and 53 polymorphic sites. Haplotype diversity, nucleotide diversity and the average number of nucleotide differences were estimated to be 0.9496 ± 0.011, 0.01407 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…This finding is consistent with archeological data and other genetic diversity studies [21,[40][41][42][43], while in this study, the haplotype diversity was higher than that found in a previous study [44], and the nucleotide diversity was lower compared with the data in a previous study [7]. The genetic diversity among the 15 Tibetan sheep populations was relatively higher compared with other sheep populations [1,44]. For instance, the haplotype diversity values of Turkish sheep breeds distributed in a Turkish population were 0.95 ± 0.01 [44].…”
Section: High Mtdna D-loop Diversity Of Tibetan Sheep Populationssupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with archeological data and other genetic diversity studies [21,[40][41][42][43], while in this study, the haplotype diversity was higher than that found in a previous study [44], and the nucleotide diversity was lower compared with the data in a previous study [7]. The genetic diversity among the 15 Tibetan sheep populations was relatively higher compared with other sheep populations [1,44]. For instance, the haplotype diversity values of Turkish sheep breeds distributed in a Turkish population were 0.95 ± 0.01 [44].…”
Section: High Mtdna D-loop Diversity Of Tibetan Sheep Populationssupporting
confidence: 93%
“…The genetic diversity among the 15 Tibetan sheep populations was relatively higher compared with other sheep populations [1,44]. For instance, the haplotype diversity values of Turkish sheep breeds distributed in a Turkish population were 0.95 ± 0.01 [44]. However, according to Walsh's work, based on the required sample size for the diagnosis of conservation units [45], a sample of 59 individuals fails necessary to support the hypothesis that individuals with unstamped ("hidden") character states exist in the population size.…”
Section: High Mtdna D-loop Diversity Of Tibetan Sheep Populationsmentioning
confidence: 88%
See 1 more Smart Citation
“…There was no specific haplogroup distribution pattern in breeds or different ecological regions. Haplogroup C sequences, which were first identified in Chinese sheep (Guo et al, 2005;Luo et al, 2005) and also detected late at low frequency in Middle Eastern and European sheep breeds (Pedrosa et al, 2005(Pedrosa et al, , 2007Pereira et al, 2006;Tapio et al, 2006;Oner et al, 2013), were found in the three breeds distributed in the hills. This result suggested a probable gene flow from northeast to southwest but not reach the low lands of Nepal.…”
Section: Haplogroup Identification and Phylogenetic Analysismentioning
confidence: 88%
“…Diversity of mitochondrial DNA (mtDNA) has been widely used to assess the origin, phylogeny and population structure of sheep breeds all over the world (Hiendleder et al, 1998a(Hiendleder et al, , 1998b(Hiendleder et al, , 2002Meadows et al, 2005Meadows et al, , 2007Pedrosa et al, 2005Pedrosa et al, , 2007Pereira et al, 2006;Tapio et al, 2006;Oner et al, 2013), specifically in China (Guo et al, 2005;Luo et al, 2005;Chen et al, 2006;Wang et al, 2007;Sulaiman et al, 2011;Zhao et al, 2011) and India (Pardeshi et al, 2007;Arora et al, 2013;Singh et al, 2013). In contrast, information on phylogeography of Nepalese sheep mtDNA is scarce.…”
Section: Introductionmentioning
confidence: 99%